Golput Dan Dinamika Demokrasi Lokal: Analisis Yuridis Terhadap Partisipasi Masyarakat Dalam Pemilihan Kepala Daerah Serentak Tahun 2024 - Rohmad Pujiyanto (PSHPM Untag Semarang, 2025)
The phenomenon of the White Group (golput) in the simultaneous Regional Head Elections (Pemilukada) in 2024 is one of the crucial issues in the development of local democracy in Indonesia. As a democratic country with the third largest number of voters in the world, the level of public participation in Pemilukada is a benchmark for the success of democratic consolidation. Golput , which is essentially a constitutional right of citizens not to exercise their right to vote, has serious implications for the legitimacy of election results and the quality of local government. This study aims to analyze (1) the regulation and position of people's voting rights as constitutional rights in a juridical perspective; (2) the main factors that affect the high number of golput in the 2024 simultaneous elections; and (3) the juridical implications of the golput phenomenonÂ on the legitimacy of election results and the quality of local democracy, as well as strategic steps to increase public political participation. The method used is normative juridical with legislative, conceptual, and case approaches. The results of the study show that the right to vote is a constitutional right guaranteed by the 1945 Constitution, but in practice public political participation is influenced by structural, cultural, and technical factors, ranging from low political literacy, the rampant phenomenon of single candidates, to public distrust of the integrity of election organizers. The high numberÂ of golputs has implications for the decline of the legitimacy of elected local governments, weakens the quality of local democracy, and exacerbates the crisis of political representation. This research emphasizes the importance of strategic steps in the form of strengthening political education, transparency of the electoral system, candidacy reform, the use of technology, and increasing the role of political parties and election organizers in encouraging public participation